Two-chambers soft actuator bending and rotational properties for underwater application - Muhammad Rusydi Muhammad Razif; Ahmad Athif Faudzi; Ili Najaa Aimi Mohd Nordin; Tariq Rehman; Dyah Ekashanti Octorina Dewi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents a study on bending and rotational properties of two-chambers soft actuator for underwater application. Previous study demonstrated the actuator characteristics required to optimize the bending performance and its potential to perform underwater because of the actuator material. However, there is less study of the actuator performance underwater as well as how the actuator tips rotating during actuator bending motion. In this paper, three tests have been proposed which are comparisons of bending angle simulation and experiment in air environment, bending angle performance in air and underwater environment as well as rotational angle of actuator tip in air environment. The bending angle of soft actuator is measured based on displacement in horizontal and vertical axis and for rotational angle, gyro sensor has been used. Based on the analysis, it is proven that the fabricated soft actuator performs almost similar trend to the simulation. It is also demonstrated that the actuator performs almost double bending motion underwater environment compared to in air environment at the same pressure, and the actuator is able to rotate 90º in air environment with the supplied pressure 52 kPa.